A ASSISTÊNCIA AO IDOSO: ATUAÇÃO DO PROGRAMA DE ATENÇÃO AO IDOSO (P.A.I.) DA UNIJUÍ EM UMA UNIDADE BÁSICA DE SAÚDE (UBS) DO MUNICÍPIO DE IJUÍ - Franz, Ligia B. B.; Berlezi, Evelise M.; Oliveira, Karla R. d.; Eickhoff, Heloísa M.; Bandeira, Vanessa A. C. (Salão do Conhecimento, 2013)
Resumo